A Cree Hermeneutical Study of Grettis saga - Neal Johansson 1970- (2025)
My central thesis is that a Cree hermeneutical study of Grettis saga brings unique insights into the text. Following Neil Price (Price, 2019), I want to draw upon elements of beliefs and narratives of Indigenous people from North America. In particular, Cree culture will be drawn upon to animate the interpretation of old Norse literature, focusing on Grettis saga. It has been over a millennium since Iceland adopted Christianity, and some of the knowledge and experiences regarding pre-Christian beliefs has been lost as a living, narrative memory. In contrast, pre-Christian Cree beliefs, despite colonial disruption, are still intact, and can be used to amplify the understanding of Grettis saga. Through a Horizontverschmelzung (Gadamer, 1960) between Cree narrative memory and the narrative structure of Grettis saga, the following themes will be explored: 1. the decline of the heroic ideal, 2. indigeneity and Icelandic connections to land and space in Grettis saga, 3. Gadamer’s notion of play as found in Ayȃs (Cree folk hero) and Grettir’s exile and outlawry, 4. confronting monstrosity (Glámr and wȋhtikowak), and 5. magic and feuds in the context of Þuríðr’s curse upon Grettir. Í þessari ritgerð er fjallað um hvernig túlkunarfræði Cree frumbyggja færir einstaka innsýn í Grettis sögu. Út frá kenningum Neil Price, 2019 eru notaðir þættir úr viðhorfum og frásögnum frumbyggja í Norður-Ameríku. Sérstaklega verður gripið til menningar Cree frumbyggja til að auðga túlkun á íslenskum fornbókmenntum með áherslu á Grettis sögu. Meira en þúsund ár eru liðin síðan Ísland tók upp kristna trú og hefur hluti af þeirri þekkingu og reynslu á fornkristnum viðhorfum glatast sem lifandi frásagnarminni. Aftur á móti er trú Cree frumbyggja enn sú sama og var fyrir tíma kristni, þrátt fyrir að hafa orðið fyrir truflun á nýlendutímanum, og er hægt að nota hana til að auka skilning á Grettis sögu. Í gegnum Horizontverschmelzung, Gadamer, 1960 á milli frásagnaminnis Cree frumbyggja og frásagnarbyggingar Grettis sögu verða eftirfarandi þemu ...